The evaluation of sea cucumber (Acaudina leucoprocta) peptide on sex hormone regulation in normal and premature ovarian failure female mice. Issue 3 (16th January 2023) - Luo, Xianliang; Liu, Wangxin; Zhao, Minjie; Wang, Jing; Gao, Xinchang; Feng, Fengqin
Abstract : The effect of SCP on hormone regulation in normal and POF female mice was investigated. We found that SCP potentially acts as a hormone-like supplement for POF mice. Abstract : Sea cucumber peptides (SCPs) have various functional activities. However, studies to evaluate the efficacy and safety of SCPs from the perspective of sex hormones are still lacking. In this study, normal and premature ovarian failure (POF) female mice were used to assess the effect of SCPs on the sex hormones. The ovarian and uterine indices were not influenced by SCP both in normal and POF mice. In normal mice, SCP showed no significant impact on the estrous cycle, ovarian, uterine morphology, sex hormone levels, and sex hormone synthesis-related genes of the ovary. However, 0.6 mg per g bw dosage of SCP (SCPH) statistically increased mapk1 expression on normal mice hypothalamus. In POF mice, SCPH played a more positive role than a low dosage of SCP (0.2 mg per g bw). SCP ameliorated POF-induced estrous cycle disturbances and significantly increased serum estradiol, testosterone, and AMH levels. Moreover, SCP increased the synthesis of the sex hormone by upregulating the expression of StAR, Fshr, and Cyp19a1 in the ovary, which might be due to the activation of the cAMP-related signaling pathways. The upregulation of mapk1, Esr1, and Gnrh was also observed in the hypothalamus. Together, SCP is safe for normal female mice and seems to have positive effects on POF mice from sex hormone regulation. However, the risk of excessive supplementation of sex hormones induced by the SCP intake in POF mice needs to be further explored.